Análises ômicas de duas bactérias potencialmente probióticas revelam novas bacteriocinas de Lactobacillus rhamnosus L156.4 e proteínas com potencial imunomodulador de Lactococcus lactis NCDO 2118 - Letícia de Castro Oliveira (2019)
The bacteria of the genus Lactobacillus and Lactococcus stand out in the group of lactic acid bacteria, both because they have been used in the food industry for years, and because they present new strains characterized as probiotic. Using in silico and in vitro analyzes, we searched for genes and proteins involved in the probiotic effect of Lactobacillus rhamnosus L156.4 and Lactococcus lactis subsp. lactis NCDO 2118. The analyzes focused on studies of antagonistic activity; preliminary analyzes mimicking the gastrointestinal tract in vitro, in addition to the prediction of genes related to probiosis, respectively. In the studies with L. rhamnosus L156.4, its antagonistic spectrum was evaluated, where genes and proteins related to bacteriocins were predicted, in addition to the characterization of cell and supernatant activity. By means of these analyzes the broad antagonistic spectrum of this strain was observed, even in the use of the supernatant alone, which did not show inhibition only against gram-negative species used in the study. Being the first report of a Lactobacillus isolated from feces of NIH mice, this strain stands out for presenting a significant probiotic characteristic. In the study with the L. lactis NCDO 2118 lineage, another 15 complete genomes available in the NCBI were used to perform comparative genomic analyzes. These analyses highlighted the great similarity between L. lactis NCDO 2118 and L. lactis KF147 strains, which share the same genomic island characterized as metabolic and symbiotic. In the evaluation of the probiotic characteristics, NCDO 2118 presented a certain survival (48%) to the gastric environment, adhesive characteristics (52%), besides the presence of bacteriocins and related proteins. In silico analyses did not predict any gene related to resistance nor regions acquired by horizontal gene transfer or even the presence of islands of resistance to antibiotics. The proteomics approach has added potential data that may be directly linked to the anti-inflammatory and immunomodulatory capacity of L. lactis NCDO 2118, however, an in-depth analysis is necessary to reach a conclusion. Thus, the results showed possibilities that still need to be studied in an integrated way, moving towards other omic approaches, such as transcriptomics, for example. Through it, we can expose this strain under study to specific conditions, thus evaluating the expression of genes through specific situations.